2012
DOI: 10.1007/s13197-012-0662-7
|View full text |Cite
|
Sign up to set email alerts
|

Effects of gamma irradiation and/or cooking on nutritional quality of faba bean (Vicia faba L.) cultivars seeds

Abstract: The effect of gamma irradiation (0.5 and 1.0 kGy) and/or cooking on the proximate composition, mineral content, tannin content, phytic acid content and the in vitro protein digestibility (IVPD) of two Sudanese faba bean cultivars (BB7-S1 and SH-S2) was investigated in the present study. The results obtained revealed that gamma irradiation and/or cooking treatments have slight effect in chemical composition and mineral content, while they caused significant (P ≤ 0.05) reduction on tannin content for both cultiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
39
0
3

Year Published

2012
2012
2021
2021

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 22 publications
2
39
0
3
Order By: Relevance
“…There was a slight decrease noted in both varieties when dosing with 0.5 kGy (Osman et al 2014). Mixed results were noted for gamma irradiation of two faba bean cultivars, with the higher dose (1 kGy) causing an increase in phytate in one variety and a significant decrease in the other.…”
Section: Irradiationmentioning
confidence: 82%
“…There was a slight decrease noted in both varieties when dosing with 0.5 kGy (Osman et al 2014). Mixed results were noted for gamma irradiation of two faba bean cultivars, with the higher dose (1 kGy) causing an increase in phytate in one variety and a significant decrease in the other.…”
Section: Irradiationmentioning
confidence: 82%
“…Moreover, most of the previous studies stated that the nutritional and functional characteristics of grains are improved after radiation treatment particularly at low doses (Mukisa et al., ; Hassan et al., ; Osman et al., ; Mahmoud et al., ). However, the safe recommended gamma doses for elimination pest as well as to maintain the quality of the products should not exceed 10 kGy (Mbarki et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Domestic processing techniques have been found to reduce significantly the levels of phytates and tannins by exogenous and endogenous enzymes formed during processing. Reductions of such antinutritional factors by processing methods such as gamma irradiation, dehulling, soaking, sprouting, cooking, malting and fermentation have been documented by many researchers (Abdelhaleem et al 2008;Bains et al 2011;Ertas and Turker 2012;Gupta and Nagar 2012;Idris et al 2005;Obizoba and Atii 1994;Osman et al 2012) and still progressing. It has been reported that germination of various pearl millet cultivars increased significantly the HCl-extractable parts of both major and trace minerals, and also reduced significantly (P≤0.01) the phytic acid and polyphenols contents of millet cultivars (AbdelRahaman et al 2007).…”
Section: Introductionmentioning
confidence: 99%